Faktor-Faktor yang Mempengaruhi Kesulitan Belajar IPS di MTs Swasta Darul Ulum Budi Agung Kota Medan - Amini, Amini; Simamora, Sari Kurniah; Dawani, Syafitri Revi; Zanisti, Haryati; Ratih, Sasika; Maskuri.S, M. Irham (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Learning as a business process carried out by someone to obtain a new behavior change as a whole. The teacher's ability to use instructional media aims to make students active and easy to absorb material. Learning activities do not always run straight, there are several obstacles that make students experience difficulties in the learning process, including social studies learning at Darul Ulum Budi Agung Private MTs, Medan City. This study aims to find out about the factors that influence social studies learning difficulties by using qualitative research methods. In the research results obtained, there are two influencing factors, namely internal factors which come from students' learning interests, the effectiveness of the teacher in making the learning process interesting, and external factors in the form of coming from the role of parents in controlling student learning at home. Keywords: Factors, Learning Difficulties, and IPS